Dynamic Adverse Selection: A Theory of Illiquidity, Fire Sales, and Flight to Quality - Guerrieri, Veronica; Shimer, Robert (American Economic Review, 2014)
We develop a dynamic equilibrium model of asset markets with adverse selection. There exists a unique equilibrium in which better quality assets trade at higher prices but with a lower price-dividend ratio in less liquid markets. Sellers of high-quality assets signal quality by accepting a lower trading probability. We show how the distribution of sellers' private information affects an asset's price and liquidity, how a change in that distribution can cause a fire sale and a flight to quality, and how asset purchase and subsidy programs may raise prices and liquidity and reverse the flight to quality. (JEL D82, G12)